Congenital Intracranial Tumors: Prenatal Diagnosis by Fetal Magnetic Resonance Imaging - Jing‐Ya Ren; Hui Ji; Ming Zhu; Su‐Zhen Dong (iRADIOLOGY)
ABSTRACT Fetal intracranial tumors are rare, accounting for approximately 0.5%–1.9% of all pediatric tumors, though the true incidence may be underestimated. These tumors often present with distinct histopathological features, imaging characteristics, and clinical behavior compared to their postnatal counterparts. This review summarizes the current understanding of the prenatal diagnosis and characterization of fetal brain tumors, with a particular focus on the role of fetal magnetic resonance imaging (MRI). We discuss the advantages of advanced MR sequences in enhancing lesion detection and anatomical delineation following suspicious findings on obstetric ultrasound. Common tumor types encountered in utero—including teratomas, astrocytomas, medulloblastomas, choroid plexus papillomas, and craniopharyngiomas—are reviewed in terms of imaging features, differential diagnosis, and clinical implications. Furthermore, the review addresses the diagnostic challenges, prognostic considerations, and the potential role of fetal MRI in guiding perinatal management and parental counseling.